Cation exchange capacities of soil organic matter fractions in a Ferric Lixisol with different organic matter inputs - Oorts, K.; Vanlauwe, Bernard; Merckx, Roel (Elsevier, 2003)
Soil organic matter (SOM) has an important effect on the physicochemical status of highly weathered soils in the tropics. This work was conducted to determine the contribution of different SOM fractions to the cation exchange capacity (CEC) of a tropical soil and to study the effect of organic matter inputs of different biochemical composition on the CEC of SOM. Soil samples were collected from a 20-year-old arboretum established on a Ferric Lixisol, under seven multipurpose tree species: Afzelia africana, Dactyladenia barteri, Gliricidia sepium, Gmelina arborea, Leucaena leucocephala, Pterocarpus santalinoides, and Treculia africana. Fractions were obtained by wet sieving and sedimentation after ultrasonic dispersion. Relationships between CEC and pH were determined using the silver thiourea-method and were described by linear regression. The CEC of the fractions smaller than 0.053 mm was inversely related to their particle size: clay (< silt silt (0.02–0.053 mm), except for the soils under T. africana, D. barteri, and L. leucocephala, where the CEC of the fine silt fraction was highest or comparable to the CEC of the clay fraction. The clay and fine silt fractions were responsible for 76–90% of the soil CEC at pH 5.8. The contribution of the fine silt fraction to the CEC at pH 5.8 ranged from 35 to 50%, which stressed the importance of the fine silt fraction for the physicochemical properties of the soil. Differences in CEC between treatments for the whole soil and the fractions could be explained by the differences in carbon content. Except for the intercept for the clay fraction, SOM had a significant (P<0.001) contribution to both the intercepts (=estimated CEC at pH 0) and slopes (=pH-dependent charge) of the CEC–pH relationships for the whole soil and the fractions. The CEC of SOM at pH 5.8 varied between 283 cmolc kg−1 C for particulate organic matter, and 563 cmolc kg−1 C for the fine silt fraction. The biochemical composition of the organic inputs did not have an important effect on the CEC of SOM. In total, SOM was responsible for 75–85% of the CEC of these soils.